Perceptions on money creation and impact of accounting treatment for commercial banks’ money lending activities in Malaysia - Hossain, Md Shamim (2018)
It has been empirically proven from earlier study that commercial banks can individually create money when they extend a new loan. When banks extend new loans they do not need to wait for the customers to make deposits, rather they use a simple accounting entry to create a loan and transfer the loan amount into the borrower’s account. This easy credit creation was one of the major reasons for the Global financial crisis 2007/2008. Banks continue to create money through lending in this manner because neither consumers nor governments have called them on it over the decades. In addition, excess supply of money as a result of accumulated commercial banks’ deposit could lead to devaluation of the Malaysian currency. Excessive money supply through accumulated credit creation may result in inflation. In fact, the relationship between debt, money supply and inflation is not only true for Malaysia but also for other countries as well. More so, a large portion of money in Malaysia is backed by debt. From the monetary balance sheet of the Ringgit it is apparent that fiat money is 99.6% backed by debt. Commercial banks’ current money lending practice leads to development of credit creation which indicates that there are threats that may lead to potential financial crisis. This study aims to explore the perception of stakeholders on the impact of the accounting treatment on commercial banks’ money lending activity. Phenomenological approach has been employed to explore the perceptions of stakeholders through sharing of their experiences. A semi-structured interview approach has been used to collect the data. Seven individuals from different stakeholder groups have been interviewed with their prior consent. For the data analysis, this study has adopted the inductive thematic approach. Findings of the study show that perceptions on money creation are influenced by the respondents’ own understanding and awareness on the research issue. Respondents agreed on the accounting treatment (debit Loan and credit Deposits) but they explained the impact of this accounting treatment in different ways. There is a strong indication that money creation is happening in Malaysia like in other countries and it is happening through accounting treatment in commercial banks money lending activity. In addition, having the opportunity to use the accounting treatment, commercial banks can create money as they want and hence, the excess money created can create inflation and consequently may give rise to a potential financial crisis. Contrary to this belief, it has been argued that money creation is the result of the systematic approach of fractional reserve banking in Malaysia. According to this argument, money creation is not a threat to the economy as long there is a strong controlling role by Bank Negara Malaysia (BNM). Therefore, it is apparent from the respondents’ discussion that money creation will pose a big challenge to the economy if the controlling role of BNM weakens. In addition, respondents believed that accounting treatment for commercial banks’ money lending activity has several impacts on the economy. First, respondents claim that money creation through lending is a big fraud because only private commercial banks can use this accounting treatment (debit the loan and credit customer account/deposit) while no other institutions can use this accounting treatment. Secondly, respondents stated that this lending system along with the accounting treatment has created a debt based monetary system. This is because, during the accounting treatment, there is creation of matching deposit for extended loan and, hence, there is no real money is involved which implies that using this accounting entry allows commercial banks to create money without having money in the first place. More so, this research has also uncovered respondents’ opinions on other possible alternatives for alignment of accounting treatment of commercial banks’ money creation. Respondents suggested two proposals. A few respondents have the opinion that fiat money should be removed from the monetary system and money backed by real assets like gold and silver should be issued and controlled only by BNM. Along with the above alternative, other respondents highlight that the accounting entry for commercial banks’ money lending needs should be similar to the accounting entry of non-bank or trading institutions. Hence, the scope of commercial banks to create money in the lending system will be reduced. A study of stakeholders’ perception is of crucial importance for money lending activity. In addition, findings of this study may stimulate the chief regulatory body like BNM, the central bank of Malaysia, to be more cautious in controlling commercial banks’ money lending activity in order to prevent the future crisis. Furthermore, the findings may help to explain conflicting concepts of accounting treatment of money lending activities for Fractional Reserve Banking (FRB) under current commercial banks’ practice as compared to the explanations given in text books. Finally, in view of the scarcity of literature on this research matter, this research can become the basis of essential study for future research. In addition, future studies can look at views of the key regulator (e.g. BNM) on this research issue along with the other respondents’ arguments. Since the practical operation is different from the academic explanation on this research issue; hence, further research can be carried out to explore the practical aspect on this research matter which may provide a more comprehensive view of money creation through the accounting treatment.